MEMPREDIKSI ORIENTASI PERILAKU KONSUMEN PASCA PANDEMI COVID19 - Hasyim, Hasyim; Anindita, Rina; Dammar, Baharuddin; Ayasofia, Fitri (Jurnal Pengabdian Masyarakat AbdiMas, 2020)
Being isolated  in a certain period of time will affect the level of affection and level of cognition, as well as behavior. Understanding of this becomes the reasons to conduct training  in order to  predict the orientation of people consumption preferences after Covid19. The purpose of the training is to provide understanding of the small and medium-sized business of the consumers orientation  after covid19, and prepare activities to get started their business eficiently and effectively. The method used in training is the online method, collecting data using a survey method using a closed questionnaire to capture the direction of community preferences after covid19 has passed. Questioners spread to the community at several research sites such as Jakarta, Makassar, Aceh, Bandung.  the training participants involved 220 respondents, consisting of, 50.7% women and 49.3% Male. The results show that people preferences after the Pandemic announced focusing in 3 (three) industrial sectors, which are, the Traveling Services Sector and Tourism Services (Pure Services), the Culinary Services Sector prioritizing culinary favorites before the pandemic (Hybrid services) and the Beauty Care services sector, and Health care (pure services) The implication of the findings shows that entrepreneurs are preparing their business activities in 3 sectors which are  traveling and tourism, culinary, and health care. Keywords: isolation, covid19, prediction, preferences